Critical appraisal of extended-release hydrocodone for chronic pain: patient considerations - Gould HJ III; Paul D (Dove Medical Press, 2015)
Harry J Gould III,1,3–7 Dennis Paul1–8 1Department of Neurology, 2Department of Pharmacology and Experimental Therapeutics, 3Department of Internal Medicine, Section of Physical Medicine and Rehabilitation, 4Department of Anesthesiology, 5Neuroscience Center of Excellence, 6Center of Excellence for Oral and Craniofacial Biology, 7Pain Mastery Center of Louisiana, 8Alcohol and Drug Abuse Center of Excellence, Louisiana State University Health Sciences Center, New Orleans, LA, USA Abstract: Opioid analgesics are currently the most effective pharmacologic option for the management of both acute and chronic forms of moderate-to-severe pain. Although the “as-needed” use of immediate-release formulations is considered optimum for treating acute, painful episodes of limited duration, the scheduled dosing of extended-release formulations with immediate-release supplementation for breakthrough pain is regarded to be most effective for managing chronic conditions requiring around-the-clock treatment. The recent introduction of extended-release formulations of the opioid analgesic hydrocodone potentially broadened the possibility of providing pain relief for individuals for whom current formulations are either ineffective or not tolerated. However, reaction to the approval of the new formulations has fueled controversy over the general safety and need for opioid medications, in light of their potential for misuse, abuse, diversion, and addiction. Here, we discuss how the approval of extended-release formulations of hydrocodone and the emotionally charged controversy over their release may affect physician prescribing and the care available to patients in need of chronic opioid therapy for the management of pain. Keywords: opioid analgesics, patient risks, patient benefits, misuse, addiction